Cellular and molecular features of axon collaterals and dendrites. - Acebes, A.; Ferrus, A. (Trends in Neurosciences, 2000)
Neural geometry is the major factor that determines connectivity and, possibly, functional output from a nervous system. Recently some of the proteins and pathways involved in specific modes of branch formation or maintenance, or both, have been described. To a variable extent, dendrites and axon collaterals can be viewed as dynamic structures subject to fine modulation that can result either in further growth or retraction. Each form of branching results from specific molecular mechanisms. Cell-internal, substrate-derived factors and functional activity, however, can often differ in their effect according to cell type and physiological context at the site of branch formation. Neural branching is not a linear process but an integrative one that takes place in a microenvironment where we have only a limited experimental access. To attain a coherent mechanism for this phenomenon, quantitative in situ data on the proteins involved and their interactions will be required.